The immaculate inning : unassisted triple plays, 40/40 seasons, and the stories behind baseball's rarest feats /: unassisted triple plays, 40/40 seasons, and the stories behind baseball's rarest feats. (2018) - Cox, Joe, 1980-
No abstract available